2020
DOI: 10.1017/s0007123420000253
|View full text |Cite
|
Sign up to set email alerts
|

Real, but Limited: A Meta-Analytic Assessment of Framing Effects in the Political Domain

Abstract: In the past three decades, scholars have frequently used the concept of framing effects to assess the competence of citizens' political judgments and how susceptible they are to elite influence. Yet prior framing studies have reached mixed conclusions, and few have provided systematic cumulative evidence. This study evaluates the overall efficacy of different types of framing effects in the political domain by systematically meta-analyzing this large and diverse literature. A combined analysis of 138 experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 57 publications
(80 reference statements)
0
30
0
Order By: Relevance
“…The summary effect was small with few significant moderators of it. The summary effect was smaller than that of a more specific metaanalysis on framing and climate change attitudes (SMD = 0.17; Li & Su, 2018), smaller than that of a meta-analysis on framing and political attitudes (positive frames vs. control: d = 0.24; Amsalem & Zoizner, 2020), and it was much smaller than that of a meta-analysis on interventions targeting pro-environmental behaviors (g = 0.45; Osbaldiston & Schott, 2012).…”
Section: Small Impact Of Interventionmentioning
confidence: 66%
“…The summary effect was small with few significant moderators of it. The summary effect was smaller than that of a more specific metaanalysis on framing and climate change attitudes (SMD = 0.17; Li & Su, 2018), smaller than that of a meta-analysis on framing and political attitudes (positive frames vs. control: d = 0.24; Amsalem & Zoizner, 2020), and it was much smaller than that of a meta-analysis on interventions targeting pro-environmental behaviors (g = 0.45; Osbaldiston & Schott, 2012).…”
Section: Small Impact Of Interventionmentioning
confidence: 66%
“…A large literature has shown that framing effects substantially affect individual-level preferences (Amsalem and Zoizner, 2020; Chong and Druckman, 2007a, 2007b; Lupia, 1994; Slothuus and de Vreese, 2010) as individuals update their preferences based on new information (Zaller, 1992). This literature has highlighted both the effect of equivalence frames, which ‘present the same information in either a positive or negative light’, and emphasis frames, which ‘vary how the information is presented and its content’ (Amsalem and Zoizner, 2020: 4; also see Cacciatore et al., 2016; Chong and Druckman, 2007b). Emphasis frames usually have a stronger effect than equivalence frames because they provide information the receivers may not possess or focus their attention on aspects they may not be attentive to when considering an issue.…”
Section: Framing Effects On Support For the Euromentioning
confidence: 99%
“…Framing effects on support for the euro Preferences for euro remain or exit are unlikely to be fixed. A large literature has shown that framing effects substantially affect individual-level preferences (Amsalem and Zoizner, 2020;Druckman, 2007a, 2007b;Lupia, 1994;Slothuus and de Vreese, 2010) as individuals update their preferences based on new information (Zaller, 1992). This literature has highlighted both the effect of equivalence frames, which 'present the same information in either a positive or negative light', and emphasis frames, which 'vary how the information is presented and its content' (Amsalem and Zoizner, 2020: 4; also see Cacciatore et al, 2016;Chong and Druckman, 2007b).…”
Section: Preferences For Eurozone Membership and Exit During The Euro Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…47. Amsalem andZoizner 2020;Chong and Druckman 2007b;Chong and Druckman 2007a;Lupia 1994;Slothuus andde Vreese 2010. 48.…”
Section: Strategic Interdependence and The Formation Of Preferencesmentioning
confidence: 99%